COVID-19 infodemic and adult and elderly mental health: a scoping review - Cássia Evangelista Delgado; Eveline Aparecida Silva; Edna Aparecida Barbosa de Castro; Fabio da Costa Carbogim; Vilanice Alves de Araújo Püschel; Ricardo Bezerra Cavalcante (SciELO, 2021)
Abstract Objective: to map scientific knowledge about the repercussions of the infodemic on adult and elderly mental health in the context of the COVID-19 pandemic. Method: this is a scoping review, developed using the Joanna Briggs Institute (JBI) methodology, which included 33 articles. These articles were analyzed according to average age, gender and education level; place and period of the studies; exposure time to COVID-19 information; main signs and symptoms related to mental health; main sources of information; suggestions for mitigating the effects of the infodemic; and knowledge gaps. Results: the most present repercussions of the infodemic on the adult and elderly mental health were anxiety, depression and stress, and the most affected group was young adults and females. Conclusion: future studies with more robust designs are needed to investigate the repercussions of the infodemic on people's mental health in the medium and long term, as well as to assess the effects, feasibility, cost-benefit and meaning of interventions in population groups, especially in the elderly population.